PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Siti nurhamidah; Sukandani, Yuni (Majalah Ekonomi, 2024)
This research aims to determine the influence of Good Corporate Governance and Corporate Social Responsibility on Company Value in Main Board Property & Real Estate Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2021-2022 Period, either partially or simultaneously. The total population is 26 companies, with a total sample of 21 companies selected using purposive sampling techniques. The data collection technique used is the documentation method. The data analysis technique uses classical assumption test analysis, multiple linear regression analysis, coefficient of determination test, with hypothesis testing using the t test and F test. Based on the test results using the F test, a significance value of 0.002 < 0.05 is obtained, so it can be concluded that overall the Board of Directors variable, Audit Committee, Independent Commissioners, and CSR are proven to have an influence on Company Value. Meanwhile, the results of the t test show that the Board of Directors has an influence on Company Value with a significant value of 0.029 < 0.05, the Audit Committee has an influence on Company Value with a significant value of 0.005 < 0.05, Independent Commissioners have no influence on Company Value with a significant value of 0.669 > 0.05, and CSR has no effect on company value with a significant value of 0.220 > 0.05. The results of this research can be used by investors and potential investors as consideration before making an investment.